2D Resistive Switching Based on Amorphous Zinc–Tin Oxide Schottky Diodes. (16th December 2019) - Casa Branca, Nuno; Deuermeier, Jonas; Martins, Jorge; Carlos, Emanuel; Pereira, Maria; Martins, Rodrigo; Fortunato, Elvira; Kiazadeh, Asal
Abstract: A room‐temperature‐processed resistive switching Schottky diode that can be operated in two distinct modes, depending solely on the choice of device initialization mode, is presented. Electroforming in the diode's reverse polarity leads to an abrupt filamentary switching with inherently long data retention at the expense of rectification. After this electroforming process, the devices may work in either a bipolar or unipolar manner with a resistance window of at least two orders of magnitude. Device initialization in the forward direction shows a smooth area‐dependent switching over two orders of magnitude, which conserves the current rectification and allows for analog control over the resistance states (dependence of device history and applied voltage stimuli). This secondary mechanism involves ion exchange or charge trapping at the Schottky interface without a contribution from the bulk (hence, it is termed 2D), which is reported for the first time for an amorphous oxide semiconductor switching matrix. Abstract : A rectifying resistive switching device, fabricated at room temperature and using a sustainable amorphous oxide semiconductor, operates independently either in digital or analog mode. The analog mode is based on a 2D mechanism, which preserves current rectification. The device promises intimate integration with amorphous oxide transistors in advanced System‐On‐Panel architecture with minimal increase of fabrication complexity.